Anomalous Structural Evolution and Glassy Lattice in Mixed‐Halide Hybrid Perovskites. Issue 21 (28th April 2022) - Shahrokhi, Shamim; Dubajic, Milos; Dai, Zhi‐Zhan; Bhattacharyya, Saroj; Mole, Richard A.; Rule, Kirrily C.; Bhadbhade, Mohan; Tian, Ruoming; Mussakhanuly, Nursultan; Guan, Xinwei; Yin, Yuewei; Nielsen, Michael P.; et al.
Abstract: Hybrid halide perovskites have emerged as highly promising photovoltaic materials because of their exceptional optoelectronic properties, which are often optimized via compositional engineering like mixing halides. It is well established that hybrid perovskites undergo a series of structural phase transitions as temperature varies. In this work, the authors find that phase transitions are substantially suppressed in mixed‐halide hybrid perovskite single crystals of MAPbI3‐x Brx (MA = CH3 NH3 + and x = 1 or 2) using a complementary suite of diffraction and spectroscopic techniques. Furthermore, as a general behavior, multiple crystallographic phases coexist in mixed‐halide perovskites over a wide temperature range, and a slightly distorted monoclinic phase, hitherto unreported for hybrid perovskites, is dominant at temperatures above 100 K. The anomalous structural evolution is correlated with the glassy behavior of organic cations and optical phonons in mixed‐halide perovskites. This work demonstrates the complex interplay between composition engineering and lattice dynamics in hybrid perovskites, shedding new light on their unique properties. Abstract : Structural phase transitions are found to be substantially suppressed in mixed‐halide hybrid perovskites of MAPbI2 Br and MAPbIBr2 (MA = CH3 NH3 + ), because of the glassy behavior of organic cations and optical phonons. A slightly distorted monoclinic phase is dominant and coexists with multiple crystallographic phases over a wide temperature range.